(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces the structure of a pseudo-dual B-algebra and some of its subsets, specifically pseudo-dual B-subalgebra and pseudo-dual B-filter. Furthermore, it presents some of their properties and gives a characterization of a pseudo-dual B-subalgebra. This study also provides the relationship between a pseudo-dual B-subalgebra and a pseudo-dual B-filter. Moreover, this paper presents a Python program that was used to perform the calculations needed to verify the example of a pseudo-dual B-algebra and to verify the independence of the axioms in a pseudo-dual B-algebra.